Balanced mix design and mechanical analysis of an AC-5 mixture - Li, Ningbo; Hao, Peiwen; Peng, Biao; Huang, Rongbin; Yang, Jilong; Yao, Yuhang; Zhang, Mengya (Frontiers in Built Environment, 2025)
To avoid deviations in volumetric parameters and improve correlation with field performance, a balanced mix design for AC-5 was made in this article. The three initial asphalt contents were determined based on engineering experience. An overlay tester (OT) test was applied to all asphalt contents. The load loss rate, crack resistance index, and critical fracture energy were selected to determine the asphalt content range, combined with the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The freeze–thaw splitting test was verified. For further mechanical research, the dynamic mechanical analyzer (DMA) dynamic modulus and fatigue tests were carried out. Finally, the hysteresis curve of a single cycle was analyzed. Based on the results, the following conclusions were obtained. Through the balanced mix design and TOPSIS analysis, the optimal asphalt content range was found to be 8.8%–9.1%. The asphalt mixture at 9.0% possessed the lowest load loss rate and crack resistance index. The critical fracture energy decreased with the reduction in the asphalt content. The split tensile strength without freeze–thaw decreased, and the freeze–thaw split tensile strength increased with increasing asphalt content. The AC-5 (9.0%) mixture possessed the highest dynamic modulus and lowest microstrain, illustrating that the mixture had the best strength and anti-reflection cracking performance. In addition, the power exponential function could be applied to predict fatigue life. Finally, the asphalt mixture at 9.0% had sufficient asphalt content, meaning that the mixture had the best bonding strength between aggregates. Higher asphalt content prevented water erosion and improved the bonding area between the asphalt and aggregate. The hysteresis curve varied according to different conditions. The stored energy W, dissipative energy ∆W and internal friction Q−1 indices were applied to evaluate the AC-5 performance through the Pearson correlation analysis. The indices had obvious regularity with stress and temperature.